Pendampingan Belajar Untuk Peningkatan Numerasi di SMP Kristen 03 Kalabahi dalam Masa Penugasan Mahasiswa Program Kampus Mengajar Angkatan IV - Yuliana Adriyanti Mowata; Jon Idrison Molina; Jeni Marianti Loban (Yayasan Literasi Sains Indonesia, 2023)
The Teaching Campus Program provides opportunities for students to learn outside the classroom by becoming teacher partners in the learning process at the educational level. Through this program the role of students is needed to provide better learning to schools and hone creativity. the numeracy skills of students at Christian Middle School 03 Kalabahi are very lacking because there are still many students who think that learning related to numeracy is boring and based on formulas and calculations. Assistance is carried out by providing material and questions and games related to the material. There are differences in the results before carrying out mentoring and after carrying out learning assistance where there is an increase in the results obtained from each student. the increase in students' numeracy skills affects two factors, namely factors from within the student and factors from outside the student. Factors from within the student can be seen from the ability to grasp, students' memory of the material being taught and also the seriousness of students in participating in the learning process. While the external factors of the students are seen in the classroom atmosphere and learning methods